The effect of using dental and oral health book on the knowledge and skills of parents with Down Syndrome children - Putri, Megananda Hiranya; Koesoemah, Hetty Anggrawati; Widyastuti, Tri (Universitas Padjadjaran, 2018)
Introduction: Down syndrome is a genetic disorder experienced by individuals due to an excess of one chromosome in the body cells as the 21st chromosome. This trisomy 21 will result in changes in physical characteristics thus affecting the dental and oral health problems of the patient. This study was a quasi-experimental study aimed to determine the effect of using the dental and oral health book on the knowledge and skills of parents with Down Syndrome children in carrying out the children’s dental and oral health care. Methods: The study design was one group pre-post test with an intervention in the form of reading a book. The sample was 36 parents of Down Syndrome children who were members of the POTADS (Persatuan Orang Tua Anak dengan Down Syndrome/Association of Parents with Down Syndrome Children) in Bandung. The statistical test used was the Wilcoxon Signed Rank Test. Result: The results showed that parents' knowledge of their Down Syndrome children’s dental and oral health care and conditions were increased after reading educational books (from (4.44 ± 1.362) and (7.47 ± 2,274) respectively, into (6.69 ± 0.856) and (9.00 ± 1,394) respectively; p < 0.05). The skills of parents on performing Down Syndrome children’s dental and oral health care were also increased, from (5.00 ± 2.014) into (8.03 ± 1.134); p < 0.05. Conclusion: The book of Down Syndrome children’s dental and oral health increased parental knowledge regarding the dental and oral health care and condition of Down Syndrome children. The book also improved the parental skills in carrying out the Down Syndrome children’s dental and oral health care.Keywords: Parental skills, book, parental knowledge, Down Syndrome, Trisomy 21.